Financial Management Behavior Dengan Financial Self-Efficacy Sebagai Variabel Mediasi - I Gusti Ayu Ratih Permata Dewi (Universitas Warmadewa, 2022)
This research aims to determine the direct and indirect effect of financial literacy, financial attitudes, financial education in the family on financial management behavior. The population of this research is active students of the Faculty of Economics and Business, Warmadewa University Class of 2019 because students have taken financial accounting and financial management courses with a total of 504 people. The researchers used the Slovin formula so that the number of samples was 100 people. Methods of collecting data using a questionnaire that was distributed directly to the respondents. This research uses Partial Least Squere (PLS) analysis method which is a structural equation model (SEM). The test results show that financial literacy, financial attitudes, financial education in the family affect financial management behavior. Financial self-efficacy is able to mediate the influence of financial literacy, financial attitudes, financial education in the family to influence financial management behavior.